Mechanism of anisotropic surface self-diffusivity at the prismatic ice–vapor interface. Issue 35 (21st September 2015) - Gladich, Ivan; Oswald, Amrei; Bowens, Natalie; Naatz, Sam; Rowe, Penny; Roeselova, Martina; Neshyba, Steven
<x xml:space="preserve">Abstract</x> Models of mesoscopic ice roughening require improved understanding of surface attachment kinetics.